Crop water use, nutrient content and uptake as influenced by irrigation and nitrogen management in potato (Solanum tuberosum) – maize (Zea mays) cropping system - VERMA, SUNIL KUMAR; IDNANI, L K (The Indian Journal of Agricultural Sciences, 2013)
Field experiment was conducted in two consecutive rabi and summer seasons at IARI, New Delhi to study the effect of methods and regimes of irrigation and levels of nitrogen on water use, nutrient content and uptake in potato–maize cropping system. Significant improvement in crop height, yield attributes, yield, nutrients uptake, consumptive use, rate of water use and soil moisture extraction were with conventional furrow irrigation, irrigation at 60 mm CPE and with integrated nitrogen supply of 120 kg N (urea) + 30 kg N (FYM)/ha . Higher nitrogen dose reduced the specific gravity of potato. The highest water-use efficiency (364.5 kg/ha-cm) was recorded with irrigation at 100 mm CPE. Irrigation methods or regimes used in potato had no effect on succeeding maize. While, application of 120 kg N (urea) + 30 kg N (FYM)/ha recorded significantly higher grain (1.57 tonnes/ha) and stover (6.41 tonnes/ha) yields and nutrients uptake; application 150 kg N/ha through urea was at par.